2019
DOI: 10.1029/2019gh000208
|View full text |Cite
|
Sign up to set email alerts
|

Supply Considerations for Scaling Up Clean Cooking Fuels for Household Energy in Low‐ and Middle‐Income Countries

Abstract: Promoting access to clean household cooking energy is an important subject for policy making in low-and middle-income countries, in light of urgent and global efforts to achieve universal energy access by 2030 (Sustainable Development Goal 7). In 2014, the World Health Organization issued "Guidelines for Indoor Air Quality: Household Fuel Combustion", which recommended a shift to cleaner fuels rather than promotion of technologies that more efficiently combust solid fuels. This study fills an important gap in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(56 citation statements)
references
References 62 publications
0
55
1
Order By: Relevance
“…These differences did not account for the differential potential for LPG adoption according to different settings and socio-economic groups (Puzzolo et al 2016;Shupler et al 2019). We acknowledge that affordability to the household, prices of competing fuels, supply-chain reliability, and last-mile distribution are all potential factors that contribute to clean fuel adoption, even in best-case scenarios of plentiful cylinder refills available in the market (Rosenthal et al 2017;Puzzolo et al 2019). We provide no estimates regarding the health equity of the policy scenarios.…”
Section: Strengths and Limitationsmentioning
confidence: 97%
“…These differences did not account for the differential potential for LPG adoption according to different settings and socio-economic groups (Puzzolo et al 2016;Shupler et al 2019). We acknowledge that affordability to the household, prices of competing fuels, supply-chain reliability, and last-mile distribution are all potential factors that contribute to clean fuel adoption, even in best-case scenarios of plentiful cylinder refills available in the market (Rosenthal et al 2017;Puzzolo et al 2019). We provide no estimates regarding the health equity of the policy scenarios.…”
Section: Strengths and Limitationsmentioning
confidence: 97%
“…The wider use of LPG for clean cooking in peri-urban/urban compared to rural LMIC settings has been documented in the literature [24,26,[40][41][42]. Reported reasons for this disparity include greater access to clean fuels in urban areas, lack of access to LPG in rural contexts, relative poverty and the opportunity costs of freely gathered biomass in rural settings [17,23,50]. In support of these hypotheses, this study found that people living in rural areas were significantly more likely to report perceiving LPG as expensive and more difficult to obtain than peri-urban households.…”
Section: Fuel Use Patterns and Their Determinantsmentioning
confidence: 99%
“…A number of countries in SSA have developed national plans to increase uptake of LPG for domestic use amongst their populations under the Sustainable Energy for All (SE4All) initiative and more recently SGD 7 [14][15][16]. LPG is an ideal clean cooking fuel to promote in many countries because it is portable; easy to store and transport; and requires much less costly infrastructure compared to natural gas or electricity, meaning that adoption can be rapidly scaled [14,17]. It is also a safe fuel (when used and regulated correctly) and provides substantial health and environmental benefits [11,14,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond these technology lessons, several implementation issues have emerged, leading HAP interventions to fall short of expectations. These include low initial adoption rates for clean fuels and stoves (Lewis and Pattanayak 2012;Mobarak et al 2012;Troncoso and Soares da Silva 2017), concomitant use of polluting stoves (stove stacking) among adopters (Masera et al 2000;Puzzolo et al 2016), and issues with supply chains and cost for both stoves and fuels (Jagger and Das 2018;Puzzolo et al 2019).…”
Section: Where Hap Programs Have Underdeliveredmentioning
confidence: 99%